Facial care products : an explorative study of consumer purchase intention using FMRI - Md Sallehan, Syazwani (2021)
Introduction: Facial care products are quickly expanding in terms of market size and global coverage, there are crucial needs for a better knowledge of consumer purchasing behaviors. The research model that was studied was a simplified form of the planned behavior theory. The Theory of Planned Behavior (TPB) was served as the primary theoretical frameworks for predicting intentions to purchase facial care products in this research. Objective: The purpose of this study was to determine the effects of perceived purchase intention on subjective norms, perceived behavioral control, and attitudes toward questionnaires and facial care products. Another objective was to examine consumers' brain responses that could modulate activity of the brain signals via functional MRI. Methodology: There were two stages, with the first being a survey of 133 participants and the second involved functional Magnetic Resonance Imaging with just eight subjects. Both designs were based on the TPB model in construct questionnaire. In stage 2, we re-used the questionnaire items that assessed participants in fMRI, which included images of global and non-global facial care products. Results: Objective 1 was not supported, as only attitude influenced purchase intention positively (β= 0.451, p< 0.01). Due to the mismatch in scoring systems, this research could not reconcile objective 1 and objective 2. We used the same questions from the questionnaire with fMRI images incalculating yes and no response. There were statistically significant findings for brain signals concerning attitude (p < 0.05 uncorrected). We observed increased activities in the left superior parietal lobule, right angular gyrus,left hippocampus, left supramarginal gyrus, right precuneus and left middle occipital gyrus area (p < 0.05 uncorrected). Conclusion: There was a limitation in terms of the products employed in the experiments. This study examined just facial care products using fMRI. Therefore, future research should duplicate this study utilizing a variety of different items like car, food or household goods.